The bioinformatics of microarrays - Sartor, Maureen (Henry Stewart Talks, 2009)
Overview of microarrays, Clustering microarray data, Clustering distance measures, Clustering methods, Classification methods, Gene set enrichment testing, Data mining, pathway, and protein interaction software, Literature mining tools, Examples of bioinformatics software tools, Sharing your data: MIAME, Microarray databases, Integration of data
Archived at 2021/02/25